Retroauricular Endoscope-Assisted Approach to the Neck: Early Experience in Latin America - Lira,Renan Bezerra (2016)
Abstract Introduction There has been a significant increase in concern towards improving aesthetic and functional outcomes without compromising the oncologic effectiveness in head and neck surgery. In this subset, endoscope-assisted and robotic procedures allowed the development of new approaches to the neck, including the retroauricular access, which is now routinely used, especially in Korea. Objectives This study aims to provide a descriptive analysis of our initial experience with retroauricular endoscope-assisted approach assessing feasibility, safety, and aesthetic results. Methods Prospective analysis of the first 11 eligible patients submitted to retroauricular endoscope-assisted approach for neck procedures in the Head and Neck Surgery Department at AC Camargo Cancer Center. Results A total of 18 patients were included in this study, comprising 7 supraomohyoid neck dissections, 8 submandibular gland excisions, 3 thyroid lobectomies, and one paraganglioma excision. There was no significant local complications, surgical accident, or need for conversion into conventional open procedure in this series. Conclusion Our initial experience has shown us that this approach is feasible, safe, oncologically efficient, and applicable to selected cases, with a clear cosmetic benefit.